Prevalence, Distribution and Associated Factors of Gingival Recession in Young Adults: A Cross-Sectional Study - Resül Çolak; Merve Küçükoglu Çolak; Ahmet Alperen Kaya (Clinical Dentistry and Research, 2026)
Background and Aim: This study evaluated the prevalence,distribution, and factors associated with Cairo classification–basedgingival recession among young adults attending a universityperiodontology clinic.Materials and Methods: This cross-sectional study included 200adults aged 18–35 years attending the Periodontology Clinic atZonguldak Bülent Ecevit University between January and March2025. Gingival recession was classified as RT1, RT2, or RT3 accordingto the Cairo classification. Demographic, oral hygiene, and periodontaldata were collected. Multivariable logistic regression identifiedfactors associated with gingival recession, while multinomial logisticregression evaluated factors associated with the RT1 and RT2–RT3groups relative to the no-recession group.Results: Gingival recession was observed in 105 participants(52.5%) and 347 of 5,435 examined teeth (6.38%). RT1 was themost prevalent recession type (68%), followed by RT2 (25.7%) andRT3 (6.3%). Recession occurred more frequently in the mandibularpremolar region. Older age (odds ratio [OR]=1.20, 95% confidenceinterval [CI]: 1.11–1.29, p